A fine needle aspiration biopsy of intraocular tumors - A. A. Yarovoy (Офтальмохирургия, 2020)
Purpose: To present our experience of fine needle aspiration biopsy (FNAB) of intraocular tumors.Material and methods: Within 3 years FNAB was performed in 154 eyes  (154  patients)  for  prognostic  (n=  121)  and  diagnostic  purposes (n=33). The mean tumor thickness in group of diagnostic FNAB was 6.0 mm (range, 2.3-10.5 mm), in prognostic – 5.5 mm (range, 2.0-11.3 mm). Transscleral, transvitreal and transcorneal FNABs were performed using our new custom designed thin-wall 25 and 27G needles by our improved FNAB  technique. All  samples were analyzed  cytologically.In  cases of uveal melanoma  (UM) genetic  testing  (GT) was performed  to estimate prognosis. Cytogenetic and molecular-genetic tests on cells and remnant liquid were held in cases of UM.Results: Cytologycally informative materials was obtained in 136 of 154 (88%) FNAB samples. Diagnostic FNAB yield was revealed to be 97% (n=32): in 20 cases UM was detected, in 8 – metastases, in 3 – intraocular lymphoma and in 1 – subretinal hemorrhage. Prognostic FNAB revealed either spindle or round-shaped cells of UM in 104 of 121 cases (informative value – 86%). No signs of tumor growth within the scleral track were seen. In 2 cases vitreous hemorrhage was seen that required vitrectomy. The average follow-up period was 11 months (3 to 41 months). No severe complications were detected.Conclusion:  Our  FNAB  improved  technique  allows  to  provide excellent tissue samples suitable for differential diagnosis and estimating prognostic with no severe complications.